2021
DOI: 10.3390/ijerph18094781
|View full text |Cite
|
Sign up to set email alerts
|

Mediating and Moderating Effects of Family Cohesion between Positive Psychological Capital and Health Behavior among Early Childhood Parents in Dual Working Families: A Focus on the COVID-19 Pandemic

Abstract: This study examined the mediating and moderating effects of family cohesion on the relationship between positive psychological capital and health promotion behaviors among dual working parents of young children during the COVID-19 pandemic. We collected data from 214 dual working parents and analyzed the results using the IMB SPSS version 26.0 software. We found that positive psychological capital had significant effects on both family cohesion (β = 0.19, p < 0.001) and health promotion behaviors (β = 0.26,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In contrast to traditional cognitive theories of depression that focus on negative factors, positive psychology suggests that depression is caused by a lack of positive resources ( Zhou et al, 2010 ). Positive psychological capital refers to a positive psychological state during an individual’s growth and development, including four core components of resiliency, optimism, hope, and self-efficacy ( Ye and Fang, 2015 ), and effectively promote healthy behaviors by helping individuals cope with challenging environments ( Cho et al, 2021 ). Also according to the interaction model of psychological resilience and the “provide timely help” model, psychological capital is a protective factor against depression in adolescents, and individuals with higher levels of psychological capital are able to use their positive abilities to cope with negative emotions, enhance their own protectiveness and adaptability to the outside world, and are less likely to experience emotional problems in risky stressful situations ( Li et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to traditional cognitive theories of depression that focus on negative factors, positive psychology suggests that depression is caused by a lack of positive resources ( Zhou et al, 2010 ). Positive psychological capital refers to a positive psychological state during an individual’s growth and development, including four core components of resiliency, optimism, hope, and self-efficacy ( Ye and Fang, 2015 ), and effectively promote healthy behaviors by helping individuals cope with challenging environments ( Cho et al, 2021 ). Also according to the interaction model of psychological resilience and the “provide timely help” model, psychological capital is a protective factor against depression in adolescents, and individuals with higher levels of psychological capital are able to use their positive abilities to cope with negative emotions, enhance their own protectiveness and adaptability to the outside world, and are less likely to experience emotional problems in risky stressful situations ( Li et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Psychological resilience, which is defined as coping, adapting, and thriving in the context of adversity ( 15 ) or quick recovery of stable functioning after exposure to trauma ( 16 , 17 ), helps avoid psychological distress in the case of disasters or disease outbreaks ( 18–21 ). PsyCap and psychological resilience thus have important implications for mental health outcomes in the context of the COVID-19 pandemic ( 22 , 23 ). For example, it has been shown that PsyCap buffered psychological distress and protected against depression and anxiety during the COVID-19 pandemic ( 11 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zeng and colleagues ( 13 ) conducted research on Chinese college students and found that family cohesion was negatively related to stress related to COVID-19. Congruently, a study from South Korea ( 14 ) reported that family cohesion had a significant mediating effect on the relationship between positive psychological capital and health promotion behaviors during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%